PEMETAAN PELANGGARAN PESERTA PENGENALAN PROGRAM AKADEMIK (PPA) DI UMS TAHUN 2014 DAN VARIASI PENANGANANNYA - Wahyudi, Agus Budi; Prayitno, Harun Joko; Nasucha, Yakub; Arifin, Zainal; Sabardila, Atiqa; Riyanto, Sugeng; Faizah, Naimul (Jurnal Penelitian Humaniora, 2014)
The study aims to describe the violations by the students of the 2014 initiation at UMS and identify their solutions by the activity coordinators and line coordinators. The primary data included the verbal abuse by the coordinators, committees, and studentsâ responses to the 2014 Academic Program Activity of Teacher and Training Education Faculty - UMS. The secondary data included the non-verbal (physical) abuse obtained from observation and interview. The data were collected through observation, inter-view and written documentation which include the results of the verbal and non-verbal strictness observation, summary of the initiation program and its regulation, and photos. The data validity used was data and data source triangulation. The data were analyzed using case study technique. The results of the study showed that there were some violations by the students during the initiation program as follows: (1) smoking a cigarette, (2) wearing a short skirt for the female, (3) wearing a transparent and tight cloth for the female, (4) not wearing a complete attribute, (5) speaking unethically or using four lette-words, (6) having a long hair beyond the ears, and (7) coming late. The solutions to the violations seemed that the line coordinators tended to permit them and they did not give any punishment so that the students kept on behaving badly. Some students thought that the team of the line coordinators were linient, particularly in giving punishment to the students who violated the regulations of the initiation program.